Self-reports of Police Speeding Stops by Race: Results from the North Carolina Reverse Record Check Survey - Tomaskovic-Devey, Donald (Journal of quantitative criminology, 2006)
Survey reports of police stops and driving behavior are a potential methodology for examining the magnitude and prevalence of the “Driving While Black” phenomena. However, estimates of the magnitude or correlates of racial disparity in police stops from self-reported survey data are potentially compromised if the accuracy of self-reports of police stops and driving behavior differ by race. We report on the results of a reverse record check survey in which we directly assess the degree and consequences of differences by race in self-reports of police stops. In our sample of drivers who had been cited for speeding in the preceding year, we found that 77% of the White respondents and 71% of the African American respondents admitted to being stopped. While both groups underreport stops, African Americans do so at a higher rate. This finding is consistent with many past studies which report stronger social desirability effects on survey responses among African Americans. Thus, survey data will tend to underestimate the magnitude of the “Driving While Black” phenomena.